Manajemen Pendidikan Karakter Melalui Pembelajaran Gamifikasi Disertai Media Video untuk Meningkatkan Pengetahuan Sejarah Peradaban Islam Siswa - Adawiyah, Rabiatul; Hakim, Lukmanul; Abdurrohman, Asep; Muthmainnah, Nur Shafiyyah (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Abstract This research was motivated by the suboptimal implementation of learning related to the History of Islamic Civilization. In fact, this learning approach has the potential to educate students' character. The implementation of history learning is expected to improve by using appropriate learning methods. This study recommends the use of gamification learning accompanied by video media. The objectives of this study are 1) to analyze students' knowledge of the history of Islamic civilization before and after receiving gamification learning with video media, and 2) to evaluate the effect of gamification learning and video media on students' knowledge of Islamic civilization. This quantitative experimental research was designed with a non-equivalent control group design with one class each in the control and experimental classes. Both received pre-tests and post-tests. The experimental class received gamification learning with video media, while the control class followed the learning usually applied by the teacher. Data collection techniques were tests, interviews and observations. The main data were in the form of test results which were analyzed to test the hypothesis with the Independent Sample T-Test. The results of the analysis stated that students' knowledge of the History of Islamic Civilization increased significantly with the implementation of gamification learning with video media compared to conventional learning with direct provision of materials by the teacher. Keywords: Gamification Learning, Video Media, Knowledge of Islamic Cultural History Abstrak Penelitian ini dilatarbelakangi oleh belum optimalnya pelaksanaan pembelajaran terkait Sejarah Peradaban Islam. Padahal, pendekatan pembelajaran tersebut berpotensi untuk mendidik karakter siswa. Pelaksanaan pembelajaran sejarah diharapkan dapat ditingkatkan dengan menggunakan metode pembelajaran yang tepat. Penelitian ini merekomendasikan penggunaan pembelajaran gamifikasi disertai media video. Tujuan penelitian ini adalah 1) menganalisis pengetahuan siswa tentang sejarah peradaban Islam sebelum dan sesudah menerima pembelajaran gamifikasi dengan media video, dan 2) mengevaluasi pengaruh pembelajaran gamifikasi dan media video terhadap pengetahuan siswa tentang peradaban Islam. Penelitian kuantitatif eksperimen ini berdesain non-equivalent control group design dengan kelas kontrol dan eksperimen masing-masing satu kelas Keduanya mendapatkan pre-test dan post-test. Kelas eksperimen menerima pembelajaran gamifikasi dengan media video, sedangkan kelas kontrol mengikuti pembelajaran yang biasa diterapkan oleh guru. Teknik pengumpulan data adalah tes, wawancara dan observasi. Data utama berupa hasil tes yang dianalisis untuk menguji hipotesis dengan Independent Sample T-Test. Hasil analisis menyatakan bahwa pengetahuan siswa tentang Sejarah Peradaban Islam meningkat secara signifikan dengan implementasi pembelajaran gamifikasi dengan media video dibandingkan dengan pembelajaran konvensional dengan pemberian materi secara langsung oleh guru. Kata Kunci: Pembelajaran Gamifikasi; Video; Pengetahuan Sejarah Kebudayaan Islam